Challenges in maintenance management for low cost flat / Mohd Farith Mohd Nazari - Mohd Nazari, Mohd Farith (Faculty of Architecture, Planning and Surveying, 2013)
This research is based on the study of the challenges of the maintenance management for low cost flat. In focused on the challenges of maintenance management for low cost flat this study due to the problem statement stated in the earlier research that are lack of financial resource and problem with building residence. The objective of the study is to identify what the problems that the maintenance management department is facing, to identify the problem that facing by a resident about maintenance and to recommend on how to overcome the problem about the maintenance management. The study conducted according to the designed methodology. In order to get the findings, a questionnaire had been designed. Besides that, an interview session with management and building resident to give additional information to the related case study. Some literature review had been done by referring to the previous study such as books, journals and website that related to the topic. Desk study on the building of the case study had been conducted. It includes the history and average capacity of the occupant in the building. The respondents for questionnaire are the management and the residence of the building. Based on the findings from the case study visit, questionnaire survey and interview, a conclusion and a recommendation had been done on the last chapter.